Peran Badan Eksekutif Mahasiswa Fakultas Hukum Dalam Membangun Budaya Anti Korupsi Di Lingkungan Kampus - Tarisa, Serli (Innovative: Journal Of Social Science Research, 2024)
Corruption is a serious threat to the development of society and the economy, including in Indonesia. In various sectors, corruption has taken root and resulted in the loss of public trust and the weakening of state institutions. In this context, higher education plays an important role in shaping the character and integrity of the younger generation. The Student Executive Board (BEM) functions as an agent of change in education and student empowerment, especially in preventing corruption through education and awareness campaigns. This study aims to analyze the role of the BEM of the Faculty of Law in preventing corruption, explore the challenges faced, and formulate strategies to increase the effectiveness of the program. The methods used include seminars, workshops, and collaboration with external institutions such as the Corruption Eradication Commission (KPK). The findings show that effective education can change student behavior, while technology and social media can expand the reach of the campaign. The results of the study are expected to contribute positively to the development of BEM and create an academic environment free from corruption, while equipping students with the integrity needed to create a better future.